Comorbidity profile in chronic brain ischemia on the background of multifocal atherosclerosis. - L. А. Dzyak; О. А. Rosytska (Medičnì Perspektivi, 2019)
Aim to evaluate the comorbidity profile in patients with chronic cerebral ischemia on the background of multifocal atherosclerosis. The study included 137 patients aged 40 to 84 years with chronic cerebral ischemia (CСI) on the background of multifocal atherosclerosis, which were divided into three clinical groups depending on the localization of vascular lesions by stenosing atherosclerosis. The co-morbidity profile and severity were evaluated using the Charlson’s index in modification of R.A. Deyo (1992). In CCI patients, regardless of the combination of vascular basins affected by atherosclerosis, a severe degree of comorbidity prevailed - the Charlson’s comorbidity index (IC) was predominantly > 5 points (84.7% of cases). In the analysis of IC in age categories, depending on the combination of atherosclerotic lesions of the vascular basins, it was found that comorbidity of severe degree (IC> 5) was predominantly represented by patients of the older age group (60-74 years), and comorbidity of moderate severity (IC≤5) – patients of middle age group (45-59 years). A median difference of 3 points in assessing the mean value of age-matched comorbidity index showed that age, as a non-modifiable risk factor, in 1/3 cases determines the comorbidity index, which depends on the number of vascular basins affected by atherosclerosis. In 2/3 of the cases it is a modified comorbid pathology. Assessment of IC in clinical groups, taking into account the nature of the disease course (p <0.05), showed a correlation between the number of atherosclerosis affected by vascular basins, the severity of the clinical course of CCI and the severity of comorbidity. The severity of comorbidity, as measured by the Charlson’s index modified by R.A. Deyo, depends on age and determines the nature of the atherosclerotic lesion, as well as the severity of the clinical course of CCI. Assessing the profile and severity of comorbidity makes it possible to influence the nature of the development and course of brain ischemia, which is caused by systemic atherosclerotic lesions of the vascular system.